Macroeconomic Variables Affecting Fish Production in Nigeria - Udoh, Edet Joshua; Akpan , Sunday Brownson (Asian Journal of Agriculture and Rural Development, 2019)
The study is an attempt to examine the influence of macroeconomic variables on the growth of fishery sub-sector in Nigeria. The study covers the period from 1961 and 2017. The results apparently revealed that aquaculture production, artisanal fish production, and total fish production, grew exponentially at the rate of 8.90%, 3.75%, and 4.25% respectively. To be more precise, various other factors like, demand shocks, food imports, and variable exchange rate, affected artisanal fish production in the long-run; while exchange rate and demand shocks were significant in the short-run period. For the aquaculture production, demand shocks, credit potential, inflation, food imports, and exchange rate were some significant policy variables in the long-run; whereas demand shocks and exchange rate were also significant in the short-run period. Finally, as far as the total fish production is concerned, demand shocks, food imports, and exchange rate were significantly trending variables, both in the short and long-run periods. To promote fish production in Nigeria, fish imports should be gradually restricted and the economic system regulated to ensure the stability of naira exchange for the US dollar.